Controle biológico e bioatividade do óleo essencial de Varronia curassavica Jacq. (BORAGINACEAE) A Raoiella indica Hirst (ACARI: TENUIPALPIDAE) - Lira, Vanessa de Araújo (2018)
The red palm mite, Raoiella indica (Acari: Tenuipalpidae) is a major pest of coconut (Cocos nucifera L.) plantations worldwide. The predatory mite Amblyseius largoensis (Acari: Phytoseiidae) is found in association with R. indica in several countries, including Brazil, and can assist in the biological control of this pest in the field. Phytochemicals can be used for pest management and are generally compatible with beneficial organisms and less harmful to humans and the environment. Varronia curassavica Jacq. (Boraginaceae) is a medicinal species native to Brazil, whose essential oil possesses bactericidal, larvicidal and fungicidal activities. However, there are no studies on the bioactivity of V. curassavica essential oil against phytophagous mites and their compatibility with predatory mites. The objective of this work was to determine the functional response of A. largoensis preying upon different developmental stages of the red palm mite and to evaluate the bioactivity of the essential oil of V. curassavica VCUR 404 access to R. indica and its selectivity to A. largoensis. Nymphs and females of A. largoensis presented type II functional response when consuming eggs, protonymphs and females of R. indica, except for nymphs of the predator consuming protonymphs of the pest that presented a type III functional response. The highest oviposition rates of A. largoensis were reached when the predator fed upon eggs and protonymphs of the pest. The essential oil of V. curassavica VCUR 404 access was toxic to R. indica (LC50 = 1.9 mg / mL and LC99 = 9.1 mg / mL) and attractive for up to 24 hours in the areas treated with its LC50 and LC75. The LC25, LC50 and LC75 of the oil reduced the growth rate of R. indica, indicating a tendency to pest extinction while the LC99 caused inviability of 80% of its eggs. However, the LC50 of the essential oil, estimated for R. indica, caused a reduction in the growth rate of A. largoensis and the LC99 caused a high mortality (> 90%). We conclude that nymphs and females of A. largoensis can contribute to the reduction of R. indica, mainly in low densities of the pest. Additionally, because it is toxic and attractive to the red palm mite, the essential oil of V. curassavica VCUR 404 access could be used as a trap to attract and kill the pest.